Skrining Lactobacillus plantarum Penghasil Asam Laktat untuk Fermentasi Mocaf - Zulafa Noor; Muhammad Nur Cahyanto; Retno Indrati; Sardjono Sardjono (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2017)
This study was aimed to select the best isolates of Lactobacillus plantarum from 6 (six) of local isolates obtained from culture collections isolated from traditional foods. Selection of isolates was based on the growth rate, the number of cells, changes in pH and lactic acid production during cell growth on the MRS-broth at 37 °C for 24 hours. The results showed that the growth rate of each isolate varied, as measured by the length of the log phase, ranging from 8-20 h. It showed that some isolates quite fast towards a stationary phase and some quite slow. The number of cell ranged from 8.81 to 9.74 log CFU/mL, while the pH at the beginning of cell growth from 5.2 to 5.8, and at the end of growth from 3.4 to 3.7. Lactic acid production by the end of the growth (24 h) is 0.76 to 0.98%. The results showed isolate of L. plantarum UA3 was best having the fastest growth rate (8 h of log phase), the highest cell number (9.74 log CFU/mL), and the highest lactic acid produced (0.92 %) for 14 h incubation on MRS-broth at 37 °C. Application of selected isolate of L. plantarum UA3 on solid substrate fermentation using media grated cassava yield in 0.92% lactic acid after fermentation for 60 h, with a cell number of 9.54 log CFU/mL. ABSTRAKPenelitian ini bertujuan untuk memilih isolat Lactobacillus plantarum terbaik dari 6 (enam) macam isolat lokal yang diperoleh dari koleksi kultur yang berasal dari makanan tradisional. Pemilihan isolat didasarkan pada kecepatan pertumbuhan, jumlah sel, perubahan pH dan produksi asam laktat selama pertumbuhan pada media MRS-broth pada suhu 37 °C selama 24 jam. Hasil penelitian menunjukkan bahwa kecepatan pertumbuhan setiap isolat bervariasi, yang diukur dari lamanya fase log, yaitu berkisar antara 8–20 jam. Ini memperlihatkan bahwa beberapa isolat cukup cepat menuju fase stasioner dan beberapa lagi cukup lambat. Jumlah sel berkisar antara 8,81–9,74 log CFU/mL, sedangkan pH pada awal pertumbuhan sekitar 5,2–5,8, dan pada akhir pertumbuhan 3,4–3,7. Produksi asam laktat pada akhir pertumbuhan (24 jam) adalah 0,76–0,98%. Dari hasil tersebut isolat L. plantarum UA3 merupakan isolat terbaik dengan fase pertumbuhan log yang tercepat (8 jam), jumlah sel tertinggi (9,74 log CFU/mL), dan menghasilkan asam laktat paling tinggi (0,92%) pada inkubasi selama 14 jam dalam media MRS-broth suhu 37 °C. Aplikasi dari isolat terpilih L.plantarum UA3 dalam fermentasi substrat padat menggunakan media kasava parut menghasilkan asam laktat sebesar 0,92% setelah fermentasi selama 60 jam, dengan jumlah sel 9,54 logCFU/mL.